The effect of the implementation of evidence-based drug formulary on antibacterial use in a private hospital at Tanjung Enim, Sumatera Selatan, Indonesia - Erna Kristin; Dwi Indria Anggraini; Jarir At Thobari; Alfi Yasmina (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
The increase of drug expenditure in the hospital has facilitated the implementation of an evidence-based drug formulary. The aim of this study was to assess the change in antibacterial use after the implementation of an evidence-based drug formulary in a private hospital at Tanjung Enim, Sumatera Selatan, Indonesia. This study used a pre-posttest design. Drug use data in the period before (2010-2011) and after (2012-2013) the formulary implementation were extracted from the hospital medical records. The drug use in the hospital before and after the implementation was compared using t-test and chi-square test, with the significance level of 0.05. Average number of drugs prescribed per prescription after the implementation was similar with that before the implementation (4.4 vs 4.6; p > 0.05). However, the proportion of generic drugs prescribed increased significantly after the formulary implementation (17.0% vs 52.7%; p < 0.05). Moreover, it was still significantly increased when the analysis was conducted only for antibacterial drugs (25.9% vs 72.0%; p < 0.05). Average drug cost per prescription was 34% lower after the intervention (p < 0.05), and the average cost for antibacterial drug was also decreased (26%). The use of antibacterial drugs was significantly decreased after the intervention (12.5% vs 6.9%; p < 0.05). The most often antibacterial drugs prescribed before the interventions were beta-lactams and macrolides; while quinolones were more increasingly used after the intervention. In conclusion, the implementation of evidence-based hospital drug formulary in a private hospital at Tanjung Enim, Sumatera Selatan significantly increase generic drug use and decreased antibacterial use and average drug cost per prescription.    Key words : drug formulary – prescribing pattern – generic drug – antibacterial – private hospital